Fatigue Damage Mechanism and Fatigue Life Prediction of Metallic Materials - Cui, Haitao; Han, Qinan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The fatigue of metallic materials stands as a pivotal challenge in engineering applications. Exploring the fatigue damage mechanism and fatigue life prediction of metallic materials is of paramount importance. This reprint includes articles that explore relevant topics, and they are intended for academic researchers, engineers, and students seeking a comprehensive understanding of the recent advancements in this field.